7
$\begingroup$

By applying the Taylor series expansion to $\ln x$, as $x \to 1$, one has the Laurent series expansion, $$ \frac1{\ln x}=-\frac1{1-x}+\frac{1}{2}+O\left(1-x\right) $$

then clearly $$ \begin{align} &\lim_{\varepsilon \to 0^+} \int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln x}\:dx=\infty \\\\&\lim_{\varepsilon \to 0^+} \int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln^2 x}\:dx=-\infty. \end{align} $$

Thus I'm designing the following related limits.

Question. Find $f_1(\varepsilon)$, $f_2(\varepsilon)$ and find a closed form of $c_1$, $c_2$ such that $$ \begin{align} &\lim_{\varepsilon \to 0^+} \left(\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln x}\:dx-f_1(\varepsilon)\right)=c_1 \tag1 \\\\& \lim_{\varepsilon \to 0^+} \left(\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln^2 x}\:dx-f_2(\varepsilon)\right)=c_2. \tag2 \end{align} $$


Edit. A complete answer is now given below.

$\endgroup$
  • 1
    $\begingroup$ i think that $f_2(\epsilon) =\frac{\log(\epsilon)+1}{\epsilon}$ but i have not the slightest clue how to determine the constant $\endgroup$ – tired Aug 17 '16 at 14:53
3
$\begingroup$

Claim. As $\epsilon \to 0$, $$ \int_{0}^{1-\epsilon} \frac{\log(1-x)}{x \log^2 x} \, \mathrm{d}x = \frac{1+\log\epsilon}{\epsilon} + \frac{\gamma - 1 - \log(2\pi)}{2} + o(1). $$

Step 1. Applying the substitution $t = -\log x$ followed by integration by parts, we have

$$ \int_{0}^{1-\epsilon} \frac{\log(1-x)}{x (-\log x)^{s+1}} \, \mathrm{d}x = \frac{\eta^{-s}}{s} \log \epsilon + \frac{1}{s} \int_{\eta}^{\infty} \frac{t^{-s}}{\mathrm{e}^t - 1} \, \mathrm{d}t, \tag{1} $$

where $\eta = -\log(1-\epsilon)$. Now we focus on the latter integral, and define

$$ I = I(\eta, s) = \int_{\eta}^{\infty} \frac{t^{-s}}{\mathrm{e}^t - 1} \, \mathrm{d}t. $$

Step 2. Next, we give an explicit formula for $I(\eta, s)$ for small $\eta > 0$. (By small, we mean $\eta \in (0, 2\pi)$.) This is easily done by mimicking the derivation of the functional equation for $\zeta$ by contour integration. To this end, we first restrict ourselves to the case $\Re(s) \in (1, 2)$ and consider the contour

$\hspace{5em}$contour

Call by $C_{\eta}$ the entire contour and by $\Gamma_{\eta}$ the circular arc. Assuming the branch cut of $\log$ as $[0, \infty)$, this can be computed as

\begin{align*} &I - \mathrm{e}^{-2\pi i s} I + \int_{\Gamma_{\eta}} \frac{z^{-s}}{\mathrm{e}^z - 1} \, \mathrm{d}z \\ &\hspace{3em} = \int_{C_{\eta}} \frac{z^{-s}}{\mathrm{e}^z - 1} \, \mathrm{d}z = 2\pi i \sum_{n \in \Bbb{Z}\setminus\{0\}} \underset{z=2\pi i n}{\mathrm{Res}} \; \frac{z^{-s}}{\mathrm{e}^z - 1} \\ &\hspace{6em} = 2i \mathrm{e}^{-i\pi s} (2\pi)^{1-s} \cos\left(\frac{\pi s}{2}\right) \zeta(s). \end{align*}

This gives

$$ I(\eta, s) = \frac{1}{1 - \mathrm{e}^{-2\pi i s}} \int_{-\Gamma_{\eta}} \frac{z^{-s}}{\mathrm{e}^z - 1} \, \mathrm{d}z + \frac{(2\pi)^{1-s}}{2\sin\left(\frac{\pi s}{2}\right)} \zeta(s) $$

Since both sides define entire functions on all of $\Bbb{C}$, this identity extends to all of $s \in \Bbb{C}$. Now we plug the power series $\frac{z}{\mathrm{e}^z - 1} = \sum_{n=0}^{\infty} \frac{B_n}{n!} z^n$ into the contour integral above to get

\begin{align*} I(\eta, s) &= \sum_{n=0}^{\infty} \frac{B_n}{n!} \frac{\eta^{n-s}}{s - n} + \frac{(2\pi)^{1-s}}{2\sin\left(\frac{\pi s}{2}\right)} \zeta(s) \tag{2} \\ &= \sum_{n=0}^{\infty} \frac{B_n}{n!} \frac{\eta^{n-s}}{s - n} + \Gamma(1-s)\zeta(1-s) \tag{3} \end{align*}

Step 3. Now we consider the case of interest, i.e., $s = 1$. Taking limit as $s \to 1$ to $\text{(2)}$, only the first 2 leading terms of the series are significant (as $\eta \to 0$) and we can easily compute $I(\eta, 1)$ as

$$ I(\eta, 1) = \frac{1}{\eta} + \frac{1}{2} \log \eta + \frac{1}{2}(\gamma - \log(2\pi)) + \mathcal{O}(\eta). $$

Therefore the claim follows by plugging this to $\text{(1)}$ and utilizing the asymptotics

$$ \frac{1+\log \epsilon}{\eta} + \frac{1}{2}\log\eta = \frac{1+\log\epsilon}{\epsilon} - \frac{1}{2} + o(1). $$


Addendum 1. As a by-product, we can compute @Marco Cantarini's integral:

$$ \int_{0}^{1} \frac{\log(1-x)}{x} \left( \frac{1}{\log^{2} x} - \frac{1}{(1-x)^2} + \frac{1}{1-x}\right) \, \mathrm{d}x = \frac{\gamma + 1 - \log(2\pi)}{2}. $$


Addendum 2. Another by-product is that, for $N \in \Bbb{Z}$ and $N-1 < \Re(s) < N$ we have

$$ \int_{0}^{\infty} x^{s-1} \left( \frac{1}{\mathrm{e}^x - 1} - \sum_{n=-\infty}^{-N} a_n x^{n} \right) \, \mathrm{d}x = \Gamma(s)\zeta(s), $$

where $a_n$ are Laurent coefficients of $\frac{1}{\mathrm{e}^x - 1}$ at $x = 0$:

$$ \frac{1}{\mathrm{e}^x - 1} = \sum_{n=-\infty}^{\infty} a_n x^n = \sum_{n=-1}^{\infty} \frac{B_{n+1}}{(n+1)!} x^n. $$

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ Beautiful answer! (+1) $\endgroup$ – Olivier Oloa Aug 18 '16 at 19:28
  • $\begingroup$ @OlivierOloa, Thank you! I am trying to see if this technique is also applicable to $s = 1$ or other integer values. I will update this if I find any. $\endgroup$ – Sangchul Lee Aug 18 '16 at 19:30
2
$\begingroup$

We can try to use your idea for the other integral. Note that $$\frac{\log\left(1-x\right)}{x\log^{2}\left(x\right)}=\frac{\log\left(1-x\right)}{\left(1-x\right)^{2}}+\frac{\log\left(1-x\right)}{x}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right) $$ so we have $$\int_{0}^{1-\epsilon}\frac{\log\left(1-x\right)}{x\log^{2}\left(x\right)}dx=\frac{\log\left(\epsilon\right)+1}{\epsilon}-1 $$ $$ +\int_{0}^{1}\frac{\log\left(1-x\right)}{x}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right)dx+O\left(\epsilon\right).\tag{1} $$ Let us define $$F\left(s\right)=\int_{0}^{1}x^{s}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right)dx $$ so if we differentiate twice $$F''\left(s\right)=\int_{0}^{1}x^{s}\left(1-\frac{\log^{2}\left(x\right)x}{\left(1-x\right)^{2}}\right)dx=\frac{1}{s+1}-\int_{0}^{1}\frac{\log^{2}\left(x\right)x^{s+1}}{\left(1-x\right)^{2}}dx $$ and we have that $$\int_{0}^{1}\frac{\log^{2}\left(x\right)x^{s+1}}{\left(1-x\right)^{2}}dx=\sum_{k\geq1}k\int_{0}^{1}\log^{2}\left(x\right)x^{s+k}dx $$ $$ =2\sum_{k\geq1}\frac{k}{\left(s+k+1\right)^{3}}=2\psi^{\left(1\right)}\left(s+2\right)+\left(s+1\right)\psi^{\left(2\right)}\left(s+2\right)$$ so integrating twice and observing that $$F\left(0\right)=\int_{0}^{1}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right)dx $$ $$=\gamma+\int_{0}^{1}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}-\frac{1}{\log\left(x\right)}\right)dx=\gamma-\frac{1}{2} $$ since $$\int\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}-\frac{1}{\log\left(x\right)}\right)dx=\frac{1}{x-1}-\frac{x}{\log\left(x\right)}+c $$ and $$F'\left(0\right)=\int_{0}^{1}\left(\frac{1}{\log\left(x\right)}-\frac{\log\left(x\right)}{\left(1-x\right)^{2}}+\frac{\log\left(x\right)}{1-x}\right)dx=\gamma-\frac{\pi^{2}}{6}+1 $$ since $$\int\left(-\frac{1}{1-x}-\frac{\log\left(x\right)}{\left(1-x\right)^{2}}\right)dx=\frac{\log\left(x\right)}{x-1}+\log\left(x\right)+d $$ we have $$F\left(s\right)=\left(s+1\right)\left(\log\left(s+1\right)-\psi^{\left(0\right)}\left(s+2\right)\right)+\frac{1}{2}. $$ From $(1)$ we get $$\int_{0}^{1}\frac{\log\left(1-x\right)}{x}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right)dx $$ $$=-\sum_{n\geq1}\frac{1}{n}\int_{0}^{1}x^{n-1}\left(\frac{1}{\log^{2}\left(x\right)}-\frac{1}{\left(1-x\right)^{2}}+\frac{1}{1-x}\right)dx $$ $$=-\sum_{n\geq1}\frac{n\left(\log\left(n\right)-H_{n}+\gamma\right)+\frac{1}{2}}{n}=\sum_{n\geq1}\left(H_{n}-\log\left(n\right)-\gamma-\frac{1}{2n}\right)$$ and the closed form of the series can be found here, so

$$\int_{0}^{1-\epsilon}\frac{\log\left(1-x\right)}{x\log^{2}\left(x\right)}dx-\frac{1+\log\left(\epsilon\right)}{\epsilon}\stackrel{\epsilon\rightarrow0^{+}}{\rightarrow}\frac{\gamma-1-\log\left(2\pi\right)}{2}.$$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Proposition $1$.$$ \lim_{\varepsilon \to 0^+} \left(\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln x}\:dx-\frac12\ln^2 \varepsilon\right)=-\gamma_1 -\frac{1}{2}\gamma^2+\frac{1}{12}\pi^2 \tag1 $$

where
$$\begin{align}&\gamma: =\lim_{n\to\infty} \left(\sum_{k=1}^n \frac{1}{k}-\ln n\right) \\ & \gamma_{1}:=\lim_{n\to\infty} \left(\sum_{k=1}^n \frac{\ln k}{k}-\frac{1}{2}\ln^2 n\right) \end{align} $$ $\gamma$ being the Euler-Mascheroni constant, $\gamma_1$ being a Stieltjes constant.

Proof. For $0<x<1$, one may observe that, $$ \begin{align} \frac{\ln (1-x)}{x\ln x}&=-\frac{\ln (1-x)}{1-x}-\frac{\ln (1-x)}{x}+\left(\frac1{\ln x}+\frac1{1-x}\right)\frac{\ln (1-x)}x \tag2 \end{align} $$ giving, as $\varepsilon \to 0^+$, $$ \begin{align} &\int_0^{1-\varepsilon}\! \frac{\ln (1-x)}{x\ln x}\:dx \\\\&=-\!\!\int_0^{1-\varepsilon}\! \frac{\ln (1-x)}{1-x}\:dx-\!\!\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x}\:dx+\!\!\int_0^{1-\varepsilon}\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!\frac{\ln (1-x)}x\:dx \\\\&=\frac12\ln^2 \varepsilon-\!\!\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x}\:dx+\!\!\int_0^{1-\varepsilon}\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!\frac{\ln (1-x)}x\:dx \\\\&=\frac12\ln^2 \varepsilon-\!\!\int_0^1 \frac{\ln (1-x)}{x}\:dx+\!\!\int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!\frac{\ln (1-x)}x\:dx+O(\varepsilon) \\\\&=\frac12\ln^2 \varepsilon+\frac{\pi^2}6+\!\!\int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!\frac{\ln (1-x)}x\:dx+O(\varepsilon). \tag3 \end{align} $$ We may then evaluate the latter integral by integrating termwise as follows, which is a valid process for the related power series, $$ \begin{align} \int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!\frac{\ln (1-x)}x\:dx&=-\sum_{n=1}^\infty \frac1n\int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}\!\right)\!x^{n-1}\:dx \\\\&=\sum_{n=1}^\infty \frac{\,H_{n-1} - (\gamma+\ln n)\,}{n} \\\\&=\sum_{n=1}^\infty \frac{\,H_n - (\gamma+\ln n)\,}{n}-\sum_{n=1}^\infty\frac1{n^2} \\\\&=\,-\gamma_1 -\frac{1}{2}\gamma^2+\frac{1}{12}\pi^2 -\frac16\pi^2 \tag4 \end{align} $$ where we have used this result and this one. Inserting $(4)$ in $(3)$ leads to $(1)$.


Proposition $2$.$$ \lim_{\varepsilon \to 0^+} \left(\int_0^{1-\varepsilon} \frac{\ln (1-x)}{x\ln^2 x}\:dx-\frac{1+\ln \varepsilon}{\varepsilon }\right)=\frac{1}{2}\gamma-\frac12\ln (2\pi)-\frac12 \tag5 $$

where $\gamma$ is the Euler-Mascheroni constant
$$\begin{align}&\gamma: =\lim_{n\to\infty} \left(\sum_{k=1}^n \frac{1}{k}-\ln n\right). \end{align} $$ Proof. One may start with an integration by parts, then as we did previously one may seperate diverging terms from converging terms, $$ \begin{align} &\int_0^{1-\varepsilon}\! \frac{\ln (1-x)}{x\ln^2 x}\:dx \\\\&=\left.-\frac{\ln (1-x)}{\ln x}\right|_0^{1-\varepsilon}-\!\!\int_0^{1-\varepsilon} \frac{1}{(1-x) \ln x}\:dx \\\\&=-\frac{\ln \varepsilon}{\ln (1-\varepsilon)}+\int_0^{1-\varepsilon}\!\! \left(\!\frac1{1-x}-\frac12\!\right)\!\frac{1}{1-x}\:dx-\!\!\int_0^{1-\varepsilon}\!\! \left(\!\frac1{\ln x}+\frac1{1-x}-\frac12\!\right)\!\frac{1}{1-x}\:dx \\\\&=-\frac{\ln \varepsilon}{\ln (1-\varepsilon)}-1+\frac{1}{\varepsilon }+\frac12\ln \varepsilon-\!\!\int_0^{1-\varepsilon}\!\! \left(\!\frac1{\ln x}+\frac1{1-x}-\frac12\!\right)\!\frac{1}{1-x}\:dx \\\\&=\frac{1+\ln \varepsilon}{\varepsilon }-1-\!\!\int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}-\frac12\!\right)\!\frac{1}{1-x}\:dx+O(\varepsilon\cdot \ln \varepsilon). \tag6 \end{align} $$ The latter integral has already been evaluated see at the end of this post: $$ \begin{align} \int_0^1\!\! \left(\!\frac1{\ln x}+\frac1{1-x}-\frac12\!\right)\!\frac{1}{1-x}\:dx&=\frac{1}{2}\gamma+\frac12\ln (2\pi)-\frac12. \tag7 \end{align} $$ Inserting $(7)$ into $(6)$ gives $(5)$.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

$\newcommand{\angles}[1]{\left\langle\,{#1}\,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{\mathrm{i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\Li}[1]{\,\mathrm{Li}_{#1}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ $\large p = 1$: \begin{align} &\int_{0}^{1 - \epsilon}{\ln\pars{1 - x} \over x\ln\pars{x}}\,\dd x = \int_{0}^{1 - \epsilon}\bracks{% {\ln\pars{1 - x} \over x\ln\pars{x}} + {\ln\pars{1 - x} \over x\pars{1 - x}}}\,\dd x + \int_{0}^{1 - \epsilon}{\ln\pars{1 - x} \over x\pars{1 - x}}\,\dd x \\[1cm] = &\ \int_{0}^{1}\bracks{% {\ln\pars{1 - x} \over x\ln\pars{x}} + {\ln\pars{1 - x} \over x\pars{1 - x}}}\,\dd x - \int_{1 - \epsilon}^{1}\bracks{% {\ln\pars{1 - x} \over x\ln\pars{x}} + {\ln\pars{1 - x} \over x\pars{1 - x}}}\,\dd x \\[5mm] - &\ {1 \over 2}\,\ln^{2}\pars{\epsilon} - \,\mrm{Li}_{2}\pars{1 - \epsilon} \end{align}


$$ \lim_{\epsilon \to 0}\bracks{% \int_{0}^{1 - \epsilon}{\ln\pars{1 - x} \over x\ln\pars{x}}\,\dd x + {1 \over 2}\,\ln^{2}\pars{\epsilon}} = -\,{\pi^{2} \over 6}\ +\ \underbrace{\int_{0}^{1}\bracks{% {\ln\pars{1 - x} \over x\ln\pars{x}} + {\ln\pars{1 - x} \over x\pars{1 - x}}}\,\dd x} _{\ds{\approx\ -0.9162}}\ \equiv\ c_{1} $$

The same procedure can be applied to the case $\ds{p = 2}$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.